Elementary School Teacher Problems in Learning to Write Narrative Text during the Covid-19 Pandemic - Ramayani, Faraditha Dwi; Rahman, Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2025)
This research is motivated by problems that arise in learning to write narrative texts during the covid-19 pandemic. Writing skills are not only about putting ideas that are in the mind into written form but also related to critical thinking so that it is not uncommon to find students who still have difficulties in learning narrative texts and teacher difficulties in teaching them. This study aims to determine the obstacles faced by elementary school teachers when teaching learning to write narrative texts during the covid-19 pandemic. Furthermore, the method used in this research is descriptive qualitative by giving questionnaires and conducting interviews. The subjects of this study were 20 elementary school teachers in Bukit Batu sub-district, Bengkalis district, Riau Province. The results of this study indicate that in general elementary school teachers are not ready to do online learning, this is because among other things that hinder the learning process is the lack of understanding of teachers and students about the use of distance learning applications. However, government support that has helped ease the burden by providing free quota subsidies to teachers, students and the availability of Wi-Fi in some areas does not seem to be able to maximize its use for online learning.